Anticipatory postural adjustments during self inflicted and predictable perturbations in Parkinson's disease. - Latash, M L (1995)
This study investigated the relation between impaired anticipatory postural adjustments and bradykinesia in Parkinson's disease. Patients with Parkinson's disease and age matched controls stood on a platform. In one series of experiments, they performed fast, discrete shoulder flexion or extension movements. In another series, they were required to press a trigger with the right thumb and thus to release a load that was suspended from a bar which they were holding in front of them in extended arms. One more series included catching a load on the same bar. Anticipatory changes in the activity of postural muscles before fast voluntary movements occurred in patients and controls although the patients showed higher variability of anticipatory patterns. During load dropping and catching, control subjects had reproducible, although smaller, anticipatory changes in postural muscle activity. Such changes were absent in all but one patient. Two sources of these postural perturbations were analysed. The anticipatory postural adjustments in different muscle groups may counteract perturbations of different origin. The distal to proximal sequencing of joint involvement in postural reactions may be related to different reference points and working points associated with these tasks compared with reaching limb movements. The deficit in anticipatory postural adjustments in Parkinson's disease is likely to be unrelated to bradykinesia and is more likely to reflect the deficits in the basic processes of preparation and initiation of a motor act.